Intersectoral linkages of Malaysian batik industry: an application of input-output analysis - Mohamad Akhir, Noor Haslina; Ismail, Normaz Wana; Kaliappan, Shivee Ranjanee; Said, Rusmawati (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper examines the contribution of batik industry to the national economy through the idea of inter-industry linkages. Batik industry’s contribution to Malaysian economy is through the performances of the manufacturing in textiles, the development of tourism with being high-valued heritage products, and to the total Malaysian craft sales. The local batik entrepreneurs also require local traders of raw materials for producing batik from abroad to the local market. These shows that batik not only plays a vital role in fostering heritage and cultural, but it has economic values via its contribution to the other production sectors in economy. However, it is difficult to measure the economic contribution of the batik industry because there is no specific data on this industry in the SME Annual Report and the Malaysian Handicraft Annual Report. Thus, we used data from Malaysian Input-Output Table 2010 to measure the industrial linkages of batik industry with other production sector in Malaysian economic structure. It is found that batik industry has backward linkages with other production sectors. This result implies that stimulating growth in the output of the batik industry would benefit other sector through positive spillover effects due to the higher demand on the output of other sectors (e.g. textiles) to be used as inputs by batik firms in producing batik.